Analyzing the perception of students regarding administrative support, educational process quality, and institutional management within universities in Romania - Dalban, Costel Marian; Bularca, Cristina Maria; Bucs, Anna; Anton, Mihail; Coman, Claudiu (Frontiers in Education, 2025)
We examine Romanian university students’ perceptions of administrative and institutional support, educational process quality, and institutional management, with a focus on how these dimensions shape overall satisfaction and trust in universities. The study is motivated by persistent challenges in infrastructure, teaching quality, transparency, and student representation in Romanian higher education. We conducted a cross-sectional, quantitative study using an online, self-administered questionnaire completed by N = 6,951 students from bachelor’s, master’s, and doctoral programs across public/private HEIs in all eight development regions of Romania. Analyses included descriptive statistics, Pearson correlations, and linear regression to assess relationships among key constructs; internal consistency was excellent (Cronbach’s α = 0.928). Student satisfaction is significantly associated with the material base, teaching quality, support for research, decision-making transparency, and the quality of administrative services. Notable correlations include: transparency with research support (r = 0.604), transparency with teaching satisfaction (r = 0.565), teaching satisfaction with study-subject relevance (r = 0.532), and material base with transparency (r = 0.589). Administrative services relate to perceptions of the material base (r = 0.489). Only ~22% report high satisfaction with the educational process, and 20.7% indicate the material base needs improvement, despite over half rating it good to very good. Findings indicate that targeted investment in infrastructure, stronger institutional transparency (including participatory governance and consistent communication), and effective student representation are pivotal to improving satisfaction.